Avaliação de colesterol e triglicerídeos séricos em cães saudáveis suplementados com ômega n-3 - Araujo, M. M G [UNESP]; Santos, T. H Y [UNESP]; Lourenço, Maria Lucia Gomes [UNESP]; Takahira, Regina Kiomi [UNESP]; Machado, Luiz Henrique de Araújo [UNESP]; Carvalho, L. R. [UNESP] (FapUNIFESP (SciELO), 2012)
The analysis of serum cholesterol and triglycerides was performed in 20 healthy mongrel dogs, 10 male and 10 female, before and after supplementation for 30 days with fatty acids of long chain polyunsaturated derived from omega-3 n (497mg docosahexaenoic acid and 780mg eicosapentaenoic acid). The serum cholesterol presented a significant reduction after supplementation in both sexes (271.6±79.8mg/dL; 236,2±67,6mg/dL, before and after supplementation respectively). Regarding serum triglycerides, there was a reduction only in females (57.8±12,1mg/dL; 45.2±7,8mg/dL, before and after supplementation respectively), with no effect of supplementation in males.
Evaluation of serum cholesterol and triglycerides in healthy dogs supplemented with ômega-3 N
Keywords: Cholesterol; Dog; Omega n-3; Triglycerides